Patterns of Political Behavior in Organization - Farrell, Dan; Petersen, James C. (Academy of Management Review, 1982)
This paper suggests that despite the current renaissance of interest in organizational power and politics, organization theory neglects individual political behavior within organizations. The need for a concern for individual political behavior is explored, and three key dimensions of political behavior are suggested: internal-external, vertical-lateral, and legitimate-illegitimate. A typology based on these dimensions is proposed, and predictions about the different types of political behavior are offered.